Connections between poverty, water and agriculture: evidence from 10 river basins - Kemp-Benedict, Eric; Cook, Simon E.; Allen, S.L.; Vosti, S.; Lemoalle, J.; Giordano, Mark; Ward, J.; Kaczan, D. (Informa UK Limited, 2011)
The authors analysed livelihood conditions in 10 river basins over three continents to identify generalizable links between water, agriculture and poverty. There were signi cant variations in hydrological conditions, livelihood strategies and institutions across basins, but also systematic patterns across levels of economic development. At all levels, access to water is in uenced by local, regional or national institutions, while the importance of national versus local institutions and livelihood strategies vary with economic development. The cross-basin analysis suggests a framework for thinking about ater-agriculture-poverty links that can inform future research and policy development.